Behavioral Circumscription and the Folk Psychology of Belief: A Study in Ethno‐Mentalizing. (17th August 2017) - Rose, David; Machery, Edouard; Stich, Stephen; Alai, Mario; Angelucci, Adriano; Berniūnas, Renatas; Buchtel, Emma E.; Chatterjee, Amita; Cheon, Hyundeuk; Cho, In‐Rae; Cohnitz, Daniel; Cova, Florian; et al.
Abstract : Is behavioral integration (i.e., which occurs when a subject's assertion that p matches her nonverbal behavior) a necessary feature of belief in folk psychology? Our data from over 5, 000 people across 26 samples, spanning 22 countries suggests that it is not. Given the surprising cross‐cultural robustness of our findings, we argue that the types of evidence for the ascription of a belief are, at least in some circumstances, lexicographically ordered: assertions are first taken into account, and when an agent sincerely asserts that p, nonlinguistic behavioral evidence is disregarded. In light of this, we take ourselves to have discovered a universal principle governing the ascription of beliefs in folk psychology.